2007
DOI: 10.1002/hyp.6624
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analysis of hydro‐climatic and vegetation condition trends in the Yellow River basin

Abstract: Abstract:Stream-gauge data indicate that the flow of the Yellow River has declined during the past several decades. Zero flow in sections of the river channel, i.e. the Yellow River drying-up phenomenon, has occurred since the 1970s. In this paper we present an analysis of changes in the spatial patterns of climatic and vegetation condition data in the Yellow River basin based on data from meteorological stations and satellites. The climatic data are from 1960 to 2000 and the vegetation condition data are from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…The change magnitude during the study period is computed as the slope of the linear regression times the length of the study period. The relative change magnitude is then calculated as the percentage of change magnitude relative to the mean value (Tang et al, 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…The change magnitude during the study period is computed as the slope of the linear regression times the length of the study period. The relative change magnitude is then calculated as the percentage of change magnitude relative to the mean value (Tang et al, 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…However, various studies have reported that a reduction in river runoff occurred as an outcome of the enhanced soil conservation in the Loess Plateau (Li et al, 2009;Gao et al, 2015;Wei et al, 2015;Liang et al, 2015). River runoff from the Loess Plateau contributes to the tributaries of the Yellow River; therefore, a reduction in runoff from the plateau will not only influence the provisioning of water for local residents, but will also affect the downstream flow in the Yellow River (Tang et al, 2008). Understanding the effects of soil conservation measures on river runoff from the Loess Plateau is important for guiding the implementation of future soil conservation initiatives (Xu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the global trend, temperatures have increased in the basin. Since the 1960s, the average air temperature has risen by more than 1°C, and even more in the Qinghai-Tibet Plateau (Tang et al 2008;Hu et al 2012). Several studies revealed permafrost degradation across the Qinghai-Tibet Plateau caused by warming during the last decades, and a continued thawing may lead to increasing emissions of greenhouse gases (Li et al 2008;Wu et al 2015).…”
Section: Climate Change and Variabilitymentioning
confidence: 99%
“…Several studies revealed permafrost degradation across the Qinghai-Tibet Plateau caused by warming during the last decades, and a continued thawing may lead to increasing emissions of greenhouse gases (Li et al 2008;Wu et al 2015). Precipitation patterns have also changed throughout the entire basin: precipitation quantities have generally decreased, but the decline is mainly concentrated in the Loess Plateau in the middle reaches, whereas the Yellow River's source region has received higher quantities of rain (Tang et al 2008). Another feature that has a direct influence on regional precipitation is the occurrence of El Niño/Southern Oscillation (ENSO) events.…”
Section: Climate Change and Variabilitymentioning
confidence: 99%